Cloning and analysis of 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase genes HsHDR1 and HsHDR2 in Huperzia serrate - Haizhou Lv; Xin Zhang; Baosheng Liao; Wanjing Liu; Liu He; Jingyuan Song; Chao Sun; Hongmei Luo; Shilin Chen (Elsevier, 2015)
We cloned and analyzed the two genes of the 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (HDR) gene family from Huperzia serrate. The two transcripts coding HDR, named HsHDR1 and HsHDR2, were discovered in the transcriptome dataset of H. serrate and were cloned by reverse transcription-polymerase chain reaction (RT-PCR). The physicochemical properties, protein domains, protein secondary structure, and 3D structure of the putative HsHDR1 and HsHDR2 proteins were analyzed. The full-length cDNA of the HsHDR1 gene contained 1431 bp encoding a putative protein with 476 amino acids, whereas the HsHDR2 gene contained 1428 bp encoding a putative protein of 475 amino acids. These two proteins contained the conserved domain of 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (PF02401), but without the transmembrane region and signal peptide. The most abundant expression of HsHDR1 and HsHDR2 was detected in H. serrate roots, followed by the stems and leaves. Our results provide a foundation for exploring the function of HsHDR1 and HsHDR2 in terpenoid and sterol biosynthesis in Huperziaceae plants.